KAJIAN FAKTOR PENENTU DAYA SAING KOTA BATU SEBAGAI DESTINASI WISATA - Myrna Sukmaratri (Jurnal Tekno Global, 2016)
The tourism sector of Batu City has great potential to be a major source of local revenue. However, there is a decline in the number of tourists from 2009-2012 with an average of 13% annually. It needs special attention because it indicates saturation to travel in Batu City. The other problems are the average length of stay of tourists in Batu is low at between 1.35 to 1.67 days. Therefore, in the development of the tourism, Batu City needs strategies to improve competitiveness focusing on the determinant factors.This study aims to determine the determinant factors of destination competitivenessbased on the determinants based on the assessment of the experts using Analytical Hierarchy Process (AHP).In this study, theoretical base used is a destination competitiveness’s model by Dwyer (2003). This model is the development of competitiveness’s model such as Porter's Diamond and destination competitiveness’s model by Crouch and Ritchie (1999).Based on the research, there are five determinant destination competitiveness factors, namely (1) Natural, (2) Artificial tourism, (3) Range of tourism activities, (4) Human Resources Development, and (5) Environmental Management.  Keywords: Destination Competitiveness, Tourism Destinations, Determinants Factors, AHP